The news of Lady Fatima (peace be upon her) in the narratives of Al-Nisaburi in his Mustadrak (Journal of Imam Al-Kadhim College, 2024)
he goal of this research is to talk about Fatima Al-Zahra and her endless virtues. She is one of the icons of women, and a unique woman in history, an example and a role model throughout time. She is a symbol of the Muslim girl who is committed to the commands of God, and she is the best of women in the world, according to the honest and trustworthy tongue, when he says: “The best of women.” There are four worlds: Maryam bint Imran, Asiyah bint Muzahim, the wife of Pharaoh, Khadija bint Khuwaylid, and Fatima bint Muhammad. She is the apple of the eye of the Prophet (may God’s prayers and peace be upon him and his family) and the delight of the guardian’s heart, the fruit of prophecy and the vessel of the Imamate, the mother of Al-Hussein and the master of the women of the two years, and she was the ideal that The divine message presented it to the woman who was formulated by the hand of divine providence to be a role model for human virtues and values. She is the one with whose satisfaction God is pleased and who is angry with her. Al-Hakim Al-Naysaburi mentioned her in his book Al-Mustadrak on the Two Sahihs, in which he addressed the hadiths that were not mentioned in Sahih Muslim and Al-Bukhari, when he mentioned her news (peace be upon her). ) From her birth until her death, who is Fatima Al-Zahra? What prevailed among the women of her time? What is its status with the Messenger of God, peace and blessings be upon him? What role did you play for Islam? Several points we highlight in this research.
Keywords: Keywords: (Mrs. Fatima, Al-Marwaiyat, Al-Naysaburi, Al-Mustadrak)